2017
DOI: 10.1042/bsr20160528
|View full text |Cite
|
Sign up to set email alerts
|

Y chromosome polymorphisms may contribute to an increased risk of male-induced unexplained recurrent miscarriage

Abstract: The present study aims to explore the relationship between the Y chromosome polymorphisms (1qh+, inv(9), 9qh+, 16qh+, group D/G, Yqh– and Yqh+) and the risk of unexplained recurrent miscarriage (URM). A total of 507 couples with URM were recruited as case group and 465 healthy couples as control group. The Y chromosome polymorphisms of the male individuals were analysed with the G-banding technique, and the results of the chromosome G-banding analysis were determined using the International Naming Standards of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 23 publications
0
9
0
2
Order By: Relevance
“…Chromosomal polymorphism, also known as chromosomal normal variation, is defined as the constant small variations in chromosome morphology, including variation in length, number and position, and is usually without obvious manifestation and pathological significance. Chromosomal polymorphism has been reported to be associated with some disorders, such as recurrent miscarriage, stillbirth, foetal death, azoospermia, and infertility [15][16][17]. In this study, 80 cases of chromosomal polymorphism were detected, while inversion variants were classified as structural chromosome rearrangements according to ISCN 2016.…”
Section: Discussionmentioning
confidence: 90%
“…Chromosomal polymorphism, also known as chromosomal normal variation, is defined as the constant small variations in chromosome morphology, including variation in length, number and position, and is usually without obvious manifestation and pathological significance. Chromosomal polymorphism has been reported to be associated with some disorders, such as recurrent miscarriage, stillbirth, foetal death, azoospermia, and infertility [15][16][17]. In this study, 80 cases of chromosomal polymorphism were detected, while inversion variants were classified as structural chromosome rearrangements according to ISCN 2016.…”
Section: Discussionmentioning
confidence: 90%
“…This result may explain some surprising results of the previous studies. Some previous studies reported that chromosomal polymorphism had a high incidence rate in infertile couples [15,24,25] and couples with recurrent miscarriage [16,17,34,35]; However, there was no apparent adverse effect in IVF treatment in some studies [12,13]. The possible mechanism is couples with chromosomal polymorphic variants may be more likely to produce sperm [32,33] and embryos [33] with abnormal chromosomal components; these abnormal chromosomic embryos can be seen as multinucleation in embryo culture [6,8]; furthermore, these embryos may lead to infertility and/or recurrent miscarriage in natural conception.…”
Section: Discussionmentioning
confidence: 99%
“…Up to 45 years, the frequency of spontaneous abortions increases by 3 times or more with age. This phenomenon can be explained by the fact that spot abortion is often caused by chromosomal diseases, the frequency of which depends on age (up to 40-45%) [6][7][8][9]. In addition, it was shown that the probability of giving birth to a child with Down syndrome at the age of 30 by the mother is about 1:2500, at the age of 31-34 -1:1200, at the age of 35-39 -1:200 [10].…”
Section: Introductionmentioning
confidence: 99%